2006
DOI: 10.2478/v10001-006-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Pesticides and Childhood Cancer Risk: Has there been any Progress in Epidemiological Studies?

Abstract: Objectives: In Europe and the United States, cancer is a major cause of death among children aged 5-14 years. The role of environmental exposure to pesticides in carcinogenesis, although strongly postulated, is still unknown. Pesticides have been used since the early days of modern agriculture. They are biologically active compounds, which may pose health risk during or after their use. Materials and Methods: Epidemiological studies focused on childhood cancer and exposure to pesticides, conducted over the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 55 publications
0
23
0
2
Order By: Relevance
“…Unfortunately, the burden of acute pesticide poisoning (both accidental and self-inflicted) in the developing world continues to exist (Ecobichon 2001), though some countries recently started to implicated in various diseases ranging from neurobehavioural disorders, developmental toxicity, endocrine disruption and impaired immune system to allergic reactions, especially of the skin. Papers investigating the increased risk of diverse types of cancer among agricultural workers have inconsistent findings and the association is still controversial (Eskenazi et al 1999;Garry 2004;Jurewicz and Hanke 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, the burden of acute pesticide poisoning (both accidental and self-inflicted) in the developing world continues to exist (Ecobichon 2001), though some countries recently started to implicated in various diseases ranging from neurobehavioural disorders, developmental toxicity, endocrine disruption and impaired immune system to allergic reactions, especially of the skin. Papers investigating the increased risk of diverse types of cancer among agricultural workers have inconsistent findings and the association is still controversial (Eskenazi et al 1999;Garry 2004;Jurewicz and Hanke 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The evidence for an association between parental occupational pesticide exposure and childhood leukemia has been limited by weaknesses of previous research methods, especially exposure assessment (Jurewicz and Hanke 2006). Two large studies did not observe an association between parental occupational pesticide exposure and childhood leukemia, however exposure in these studies was based on job title alone and exposure prevalence was very low (McKinney et al 2003; Rudant et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar review, Zahm and Ward (1998) concluded that there was some support for an association of childhood NHL and pesticide exposures, but noted that the results of most studies were based on small numbers of exposed cases. In updated reviews, Jurewicz and Hanke (2006), and Infante-Rivard and Weichenthal (2007) report on four additional studies, three of which found an increased risk for some measure of pesticide exposure and NHL and/or all lymphomas. Nasterlack (2007), in a review of studies conducted since 1998, noted that in contrast to case-control studies, cohort studies consistently showed no increased risk for NHL, but did suggest an elevated risk for Hodgkin’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…As recent reviews noted, leukemias (primarily ALL) and CNS tumors have often been associated with occupational and/or home use of pesticides in epidemiological studies (Daniels et al, 1997; Zahm and Ward, 1998; Jurewicz and Hanke, 2006; Infante-Rivard and Weichenthal, 2007; Nasterlack, 2007). Daniels et al (1997) noted that farm residence during pregnancy or childhood increased risk for primitive neuroectodermal and non-astrocytic neuroepithelial tumors, but not astrocytic gliomas, and in general did not result in increased risk of leukemias.…”
Section: Discussionmentioning
confidence: 99%